Kaizen Selection for Continuous Improvement through VSM-Fuzzy-TOPSIS in Small-Scale Enterprises: An Indian Case Study - Sunil Kumar; Ashwani Kumar Dhingra; Bhim Singh (Advances in Fuzzy Systems)
In the era of cut throat competitive market, Indian industries are under tremendous pressure to continuously reduce the cost and improve product quality. The main objective of this research paper is to provide a road map for investigating the opportunities to reduce cost and improve productivity and quality in the existing production system through the application of Lean-Kaizen concept using value stream mapping (VSM) tool at shop floor of an Indian Small-Scale Enterprise (SSE). On the basis of collected data from the selected industry, a current state map was made. After analysis, the current state map was modified to develop a future state map. By comparing current and future state map, the gap areas were identified and takt time (TT) was calculated considering actual market demand. To overcome the gap between current state map and future state map and to synchronize cycle time of each station with talk time, Kaizen event (KE) was proposed. Fuzzy technology for order preference by similarity to ideal solution (TOPSIS) was applied to prioritize and select the appropriate KE for optimized performance level. After analysis of data obtained after application of the Lean-Kaizen concept, the final improvements in terms of improved productivity (57.15%) and reduced lead time (69.47%), reduced cost (65.61%), and station cycle time (75.25%) were recorded. Through the case study drawn from realistic situations of the industry, the authors highlight that implementation of Lean-Kaizen using VSM and fuzzy TOPSIS provides improvement opportunities across the organization. The findings can inspire the SSEs to adopt the Lean-Kaizen concept for optimizing continuous improvement opportunities in their production industry. This study offers the researchers and practitioners a good example for understanding, selecting, and performing KE program. They can even attain more improvement in various areas by establishing or improving these KE programs.